Supply Chain Performance Improvement Strategy in the Packaging Industry - Rahman Soesilo (International Journal of Business and Applied Economics, 2023)
The purpose of this study is to determine what factors affect the performance of supply chain management for companies to take the right policy regarding the implementation of an effective system, in this study uses liquid literature and using Mendeley, for the factors that influence significantly Distribution, Warehousing Management Systems.  In this study, many reviewed several articles on the topic of the dependent variable and this research can be used as a reference for future research in manufacturing companies. The result that can be seen is that the warehouse management system plays a very important role in supporting the performance of supply chain management in the company. This study does not use population and sample because it is a qualitative literature review.